In the company of my sistahs - Daniels, Angie (New York : Dafina Books/Kensington Pub., 2006)
When Lisa's cancer returns, she plans to tell the women closest to her while they vacation in Jamaica. She hopes by sharing her medical condition they will make life changes. Her sister, Renee, is quite unhappy with her third husband, but feels obligated to him because he provides a lifestyle she could never achieve on her own. Kayla is an overweight mother of two. Her insecurities about her appearance allow her to accept less than what she deserves.
Nadine is an attorney who seems to have everything together. Yet she is involved in a relationship that has her questioning her sexuality. Each woman comes to the island to escape their realities and live out the Hollywood fantasy of finding romance in the Caribbean. Just when they are at each other's throats, Lisa drops the news of her illness. One year later they keep their promise to Lisa and vacation in Jamaica.
Includes reading group guide.
NLJCols20082021
Keywords: African American women -- Fiction; Vacations -- Jamaica -- Fiction; Female friendship -- Fiction; African American women; Female friendship; Vacations; Vacations -- Jamacia -- Fiction; Jamaica; Romance fiction; Fiction; Romance fiction; Love stories